Decision-Theoretic Approach To Designing Scientific Inquiry Based Learning Environment - Ting, Choo Yee (2008)
The thesis focuses on developing a learner model for INQUIRY PROCESS(INQPRO), a scientific inquiry learning environment developed within this research work.